Poly(High Internal Phase Emulsion) of 2-EHA, 2-EHMA and EGDA with naturally occurring phenolic compounds", paper presented at international conference on ?polymers for advanced technology - Ingavle, Ganesh C.; Shaikh, A. A.; Bhongale, Sunil Sitaram; Scaria, S.; Chavan, Nayaku; Qureshi, Mohammed; Ponrathnam, Surendra (Polymers for Advanced Technology, 2006)

Synthesis and characterization of cholesteric thermotropic liquid crystalline polyesters - Jadhav, Sushilkumar A.; Chougule, Rahul R.; Shinde, Yogesh A.; Chavan, Nayaku (Journal of Applied Polymer Science, 2006)
Cholesteric liquid crystalline polyesters were successfully synthesized from isosorbide, methyl hydroquinone, and isophthaloyl chloride. Homo/copolyesters were synthesized by the solution polycondensation method, for which a mild organic base such as pyridine was employed. Inherent viscosities of polyesters P-3-P-5 were in the range of 0.31-0.39 dL/g at 25 degrees C in chloroform, and polyesters P-1 and P-2 were insoluble in chloroform. Homo/copolyesters based on isosorbide, methyl hydroquinone, and isophthalic acid had thermal stability at more than 300 degrees C on the basis of 10% weight loss. The thermotropic liquid crystalline properties were examined by differential scanning calorimetry and polarizing optical microscopy. Wide-angle X-ray diffraction study demonstrated that polyesters P-1, P-2, and P-3 were semicrystalline, whereas the degree of crystallinity of polyesters P-4 and P-5 was less than 5%. Copolyester P-4 showed formation of a yellow iridescent streak at 209 degrees C on heating and development of a Grand-jean texture at 270 degrees C on heating. These are typical textures of the cholesteric liquid crystalline phase. (c) 2006 Wiley Periodicals, Inc.
Keywords: cholesteric liquid crystalline polymers (ChLCP); Differential scanning calorimetry (DSC); optical microscopy; solution polycondensation; Thermogravimetric analysis (TGA); viscosity

Removal of AS(III) and AS (V) from contaminated water sources by sorption onto novel pei-attached poly(hipe) beads", paper presented at international conference on ?role of analytical chemistry in nuclear technology? - Ingavle, Ganesh C.; Tayal, Rajeev; Shaikh, Wasif Abdul Lateef; Chaudhari, Sanjeev; Chavan, Nayaku; Rajan, Chelanattukizhakkemadath Raman; Ponrathnam, Surendra (Role of Analytical Chemistry in Nuclear Technology, 2007)

Polypyrrole functionalized with ferrocenyl derivative as a rapid carbon monoxide sensor - Paul, Santhosh; Chavan, Nayaku; Radhakrishnan, S. (Synthetic Metals, 2009)
A rapid carbon monoxide detection system was developed with the electrochemical functioncalization of polypyrrole (PPy) with ferrocenylmethyltrimethylammonium iodide (FTMA-I) as a co-dopant exhibits very high sensitivity to ppm levels of carbon monoxide gas and fast recovery under normal dry room temperature conditions. The co-dopant was synthesized mainly to incorporate into PPy electrochemically to modify the properties in order to sense carbon monoxide (CO) gas. The FTMA-I doped PPy exhibited the characteristics oxidation/reduction peaks for ferrocene in its cyclic voltammograms. The modified PPy films deposited on interdigited electrodes gave rapid sensitivity within a second to 300 ppm carbon monoxide gas and good sensitivity factor was observed even at 4 mmol of the functional groups in the polymer for 300 ppm carbon monoxide gas. This material detected the CO gas concentration as low as 100 ppm. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: carbon monoxide; Chemical sensor; conducting polymer; polypyrrole

Amino functionalized oligoimides telechelics - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Deokar, Sarika Babasaheb; Mulani, Khudbudin Baban; Ghorpade, Ravindra V.; Bhongale, Sunil Sitaram; et al. (2010)
This invention relates to a process for the preparation of amino functionalized oligoimide telechelics. More particularly it relates to a process for the preparation of soluble oligoimide prepolymers which can be used as matrix resins that can be rapidly cured to form stable polyimides with amino end functionalities. The amino functionalized oligoimide telechelics are suitable for conversion into three dimensional polymeric systems through condensation chemistry such as reaction with oligo epoxies (epoxy-imide resins), polyacids (polyamide imides) and polyhalogenated compounds (poly amine - imides) to form crosslinked structures having enhanced thermal stability and mechanical strength. The polymers prepared by the process of this invention can be used as materials in advanced composites having high temperature stability.

Synthesis and characterization of cholesteric thermotropic liquid crystalline polyesters based on isosorbide - Chavan, Nayaku (Materials Sciences and Applications, 2011)
Generally main chain cholesteric thermotropic liquid crystalline polymers are prepared form chiral dia-cid or diol monomer. But these monomers are costly. Isosorbide is chiral cycloaliphatic diol accessible from renewable resources in the form of pure enantiomers. Thus it is used to synthesize main chain cholesteric thermotropic liquid crystalline polymers. Incorporation of phenyl hydroquinone into the backbone of the main chain frustrates chain pack-ing, thus lowering the crystallinity and depressing the melting point below the degradation temperature, also improves the solubility due to disruption of packing and maintains the mechanical and thermal performance. Results: Optical microscopy study reveals that more than 50% of isosorbide content with phenyl hydroquinone and terephthalic acid showed “yellow iridescent oily streaks” with a background of mosaic/marble texture. These are the typical textures of cholesteric liquid crystalline phase. Copolyesters based on phenyl hydroquinone, isosorbide and terephthalic acid are soluble in aprotic solvents like N,N-dimethylacetamide (DMAC), dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), and N-methyl-2-pyrrolidone (NMP). Solubility increases with the content of isosorbide percent. Thermal stabil-ity of all copolyesters was more than 300˚C on the basis of 10 wt% loss. Conclusions: It was found that main chain cholesteric thermotropic liquid crystalline polymers can be prepared form chiral cycloaliphatic diol such as isosorbide. Main chain cholesteric thermotropic liquid crystalline polyesters are prepared from phenyl hydroquinone, isosorbide and terephthalic acid showed thermal stability more than 300˚C. Main chain cholesteric thermotropic liquid crystalline polymers are soluble in aprotic solvents like DMAC, DMSO, DMF and NMP
Keywords: Cholesteric; Crystallinity; differential scanning calorimetry; Inherent Viscosity; Liquid Crystalline Polymers; Optical Microscopy; Solubility and Solution Polycondensation; Thermo Gravimetric Analysis; thermotropic; Wide Angle X-Ray Diffraction

Transfer of technology (ToT) document of ethyl silicate-32 - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan, Nayaku; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhanasekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (Transfer of Technology (ToT)/ Technical Documents, 2011)

Transfer of technology (ToT) document of phenol-aniline-formaldehyde (sf-342a) resins - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan, Nayaku; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhanasekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (Transfer of technology (ToT) document, 2011)

Amino functionalized oligo polyimides with enhanced storage stability - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Mohan, Srinivasulu Reddy Krishna; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Tayal, Rajiv Kumar; Shadbar, Qureshi Mohammed; Chavan, Nayaku; Deokar, Sarika Babasaheb; et al. (WO2012090055A1, 2012)
The invention relates to an improved process for the preparation of amino functionalized oligomeric monomeric reactant type polyimides having higher stability. More particularly it relates to a process for the preparation of soluble imide prepolymers, used as matrix resins that can be rapidly cured with multi-functional moieties such as diepoxy, dicarboxyl, anhydride, diisocyanates to form crosslinked structures having enhanced thermal stability and mechanical strength.

Ethyl oligo-silicates with strong acid heterogeneous polymeric catalysts - Bevara, Madhusudana Rao; Bhongale, Sunil Sitaram; Bhosle, Sonali Madhavrao; Chavan, Nayaku; Chelanattukizhakkemadath, Raman Rajan; Deokar, Sarika Babasaheb; Dhoble, Deepa Arun; Dwivedi, Mayank; Ghorpade, Ravindra V.; Harikrishna, Reghunathan; Dhanasekharan, Janakiraman; John, Aruldoss; et al. (WO2012056290 A1, 2012)
The present invention provides a process for the synthesis of ethyl silicate with varying silica concentration, by hydrolysing ethyl silicate in varying water concentration in the presence of sulfonated catalysts having a styrene-divinyl benzene backbone. The present invention further relates to the preparation of beaded crosslinked polymers containing sulfonic acid moieties having an interconnected pore structure and surface area up to 400 m2 /g.

Photopolymerization kinetics of 2-phenylethyl (meth) acrylates studied by photo DSC - Ghorpade, Ravindra V.; Bhosle, Sonali Madhavrao; Ponrathnam, S.; Rajan, C. R.; Chavan, Nayaku; Harikrishna, Reghunathan (Journal of Polymer Research, 2012)
The present work deals with the photopolymerization of 2-phenylethyl (meth)acrylates and estimation of their kinetic parameters. Formulations were made by independently homogenizing the monomers with photoinitiators of two different classes. Two different compositions of photoinitiators were used to study the effect of concentration of photoinitiator on cure kinetics. These compositions obtained were tested for photo curing performance using differential photocalorimetry (DPC) or photo DSC under polychromatic radiation. The heat flow against time was recorded for all formulations under isothermal conditions and the rates of polymerization as well as the percentage conversions were estimated. It was observed that due to a longer timescale for reaction diffusion, the methacrylate formulations showed a higher conversion than acrylate formulations. Other parameters such as induction time, maximum rate and conversion attained as well as the time to attain peak maximum were noted. The photopolymerization and kinetic estimations of the formulations including evaluation of kinetic models are discussed.
Keywords: Bimolecular termination model; Photo DSC; Photopolymerization; Variable autocatalytic model

Synthesis and characterization of azoxy based mesogenic diols - Mulani, Khudbudin Baban; Ganjave, Nitin V.; Chavan, Nayaku (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2014)
Azoxy based rigid mesogenic diols have been synthesized using two steps. Phenol/cresol is used as starting material. Synthesized diols are characterized by IR, H-1 and C-13 NMR, and mass spectroscopic methods. Thermal properties have been determined by thermo gravimetric analysis method and crystallinity patterns have been obtained by wide angle X-ray diffiactogram. Substituted phenol (methyl) is used to study the effect of substitution on physical and thermal properties of rigid azoxy mesogenic diol. The detailed characterization of azoxy based rigid diols is reported in this communication, which is highly useful for fundamental and applied research, particularly in liquid crystals and liquid crystalline polymers. The experimental results reveal that phenol based rigid mesogenic diols have high thermal stability and degree of crystallinity than methyl substituted rigid mesogenic diols.
Keywords: Azoxy; degree of crystallinity; diol; mesogen; phenol; thermal stability

Synthesis and characterization of hypercrosslinked hydroxyl functionalized co-polymer beads - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (European Polymer Journal, 2014)
Hydroxyl functionalized beaded copolymers were synthesized from 2-hydroxy ethyl methacrylate by suspension polymerization using two different crosslinking agents (EDMA, DVB) and diluents (1,1,2,2-tetrachloroethane, 1,2-dichlorobenzene). Microporous beads with high surface area were successfully synthesized and characterized by different techniques. Maximum surface area obtained was 564 m(2)/g bearing uniform, spherical as well as non-aggregation images of beads. Thermal properties such as DTG and DSC reveal that, type of crosslinker (flexible/rigid) is major while its concentration is minor parameter that affect decomposition and softening temperature of copolymer. Swelling ratio of copolymer beads was examined as a function of crosslinker and crosslink density. Swelling behavior is in accordance with copolymer-solvent interaction parameter. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Copolymer; Morphology; surface area; Suspension polymerization; Swelling ratio

Synthesis and characterization of triad based rigid mesogenic diols derived from hydroquinone and 4-hydroxybenzoic acid - Mulani, Khudbudin Baban; Ganjave, Nitin V.; Chavan, Nayaku (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2014)
Triad based rigid mesogenic diols have been synthesized by four step synthesis method using protection-deprotection method. Hydroquinone and 4-hydroxy benzoic acid have been used as starting materials. Synthesized diols have been characterized by IR, H-1 and C-13 NMR, and mass spectroscopic methods. Thermal properties have been determined by thermo gravimetric analysis method and degree of crystallinity have been measured by wide angle X-ray technique. Substituted hydroquinones (methyl and chloro) have been used to study the effect of substitution on physical and thermal properties. Synthesis of rigid mesogenic diol monomer using p-hydroxy benzoic acid and hydroquinone is reported, which is a facile route. Hydrolysis of diacetate derivatives of rigid mesogenic diols is performed in good yields, even though two types of ester groups present in the same moiety, aromatic and aliphatic. The experimental results reveal that hydroquinone based rigid triad mesogenic diol have high thermal stability and degree of crystallinity as compared to methyl-and chloro-substituted rigid triad mesogenic diols.
Keywords: degree of crystallinity; ester hydrolysis; Mesogenic diols; spectral properties; Thermal properties

Ambient temperature photocopolymerization of tetrahydrofurfuryl methacrylate and isobornyl methacrylate: reactivity ratios and thermal studies - Rajdeo, K. S.; Ponrathnam, S.; Pardeshi, S.; Chavan, Nayaku; Bhongale, Sunil Sitaram; Harikrishna, Reghunathan (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2015)
Photocopolymerization of heterocyclic monomer namely, tetrahydrofurfuryl methacrylate with bulky bicyclic monomer, isobornyl methacrylate with different feed ratios was carried out in bulk with low concentration of an -hydroxyl ketone based photoinitiator. The ambient temperature photocopolymerization was carried out by using a UV-Visible lamp with fixed low intensity of 0.4mW cm(-2) for a period of 6min. The residual monomer remained in the polymerization process were determined by using gas chromatography. The reactivity ratio values for the two monomers were calculated from the copolymer composition data by using Fineman-Ross, Kelen-Tudos, Extended Kelen-Tudos and Mao-Huglin methods. Individually, as well as the average of all the methods revealed that the monomer reactivity ratios of tetrahydrofurfuryl methacrylate were higher than isobornyl methacrylate. The dyad sequence distribution and dyad sequence lengths were calculated using the Igarashi and Pyun method and the sequence length distribution for tetrahydrofurfuryl methacrylate was observed to be higher with an increase in its feed content. This supports the reactivity ratio studies that a higher monomer reactivity ratio value for tetrahydrofurfuryl methacrylate was observed as compared to its comonomer. The thermal studies showed that the glass transition temperatures of the copolymers increased with an increase in isobornyl methacrylate content.
Keywords: Copolymer; methacrylates; micro structure; photocopolymerization; reactivity ratios; thermal studies

Design and synthesis of cauliflower-shaped hydroxyl functionalized core-shell polymer - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (Designed Monomers and Polymers, 2015)
Conventional crosslinked polymers and homopolymers both have their own limitations. As a result, core-shell polymer was synthesized to obtain cauliflower-shaped and highly hydroxyl functionalized polymer. For the core, acrylate-based copolymers were synthesized by varying crosslinkers and porogens at different crosslink density. Owing to high surface area (554 m(2)/g), poly(MMA-co-DVB) was used as a core and low-molecular weight (24,600g/mol) poly(GMA) was used as a shell in core-shell approach. Average particle sizes of the core polymers were in the range of 15-75 mu m. In order to evaluate reactivity efficiency of core-shell polymer, hydroxyl content was evaluated with a value of 3.97mmol/g. Importantly, hydroxyl content demonstrated the successful increase in reactive sites of the core-shell polymer over conventional crosslinked hydroxyl polymer. Notably, synthesized core-shell polymer has more surface area and pore volume which substantially attributes for better polymer efficiency during application. Scanning electron microscopy images revealed the spherical, uniform, and slightly conglomerated properties of core-shell polymer. Due to higher reactivity, insolubility, and more surface area of hydroxyl functionalized core-shell polymer, its use become inevitably essential.
Keywords: C-13 solid state NMR; cauliflower-shaped porous beads; core-shell polymer; hydroxyl functionalization; surface area

Hyperhydrophilic three-dimensional crosslinked beads as an effective drug carrier in acidic medium: adsorption isotherm and kinetics appraisal - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (New Journal of Chemistry, 2015)
Conventional drug delivery materials are known to provide slow and low drug loading in aqueous medium due to the hydrophobic or less hydrophilic properties of the carrier. However, the present study explored the synthesis of cheaply available metals modified with a hyperhydrophilic polymer. Hyperhydrophilic three-dimensional crosslinked beads as a drug carrier were synthesized with desirable properties that substantially influence the polymer efficiency. These synthesized polymers were characterized for surface area, particle size, acid content and morphology, and the metal modification was evaluated to obtain an efficient polymer for drug adsorption in an acidic medium. Contact time, which significantly affects drug adsorption was comparatively evaluated using the cheaply available metals, cobalt and nickel. Interestingly, an adsorption study revealed that gradual drug loading occurs during the initial 12 h. Afterwards, adsorption increases steadily and then stabilizes. Furthermore, theoretical predictions of adsorption, including Langmuir adsorption isotherm and pseudo order kinetics, were also evaluated. Remarkably, polymer supported Co/Ni demonstrated 85 and 78% metoprolol drug adsorption, respectively, at an optimum pH of 3 after 24 h. Langmuir adsorption isotherm revealed monolayer adsorption on the polymer supported Co/Ni. Pseudo first and second order kinetics were also evaluated and demonstrated the adsorption mechanism and equilibrium adsorption capacity, respectively.

Role of interfacial tension of solvating diluents and hydrophilic-hydrophobic cross-linkers in hyper-cross-linked solid supports - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (Industrial & Engineering Chemistry Research, 2015)
The properties of a hyper-cross-linked solid support are the outcome Of the interfacial tension created by solvating/nonsolvating diluents, the hydrophilicity/hydrophobicity of the cross-linkers, and their concentrations. Interestingly, a More hydrophobic diluent and cross-linker as well as a higher concentration of cross-linker-containing copolymer revealed an increase In surface area. A high surface area and low cross-link density (CLD) polymer illustrated higher epoxy content. Importantly, maximum surface area (533 m(2)/g) Was obtained at high CLD; inversely, epoxy,content (1.83 mmol/g) was higher at low CLD polymer. Notably, greater rigidity of cross-linker and its higher concentration increased T-max and T-g; contrarily, greater flexibility of cross-linker and its concentration attenuated T-max and T-g. Thermal study demonstrated the thermostability (300 degrees C) and polymer safe temperature (220 degrees C). Indeed, a lower solubility parameter difference between polymer and swelling solvent produces a higher polymer-solvent interaction parameter, resulting in increased polymer swelling. Polymers with high surface area and low CLD demonstrated greater swelling behavior.

Synthesis and characterization of thermotropic liquid crystalline polyimides - Mane, Sachin; Rajan, C. R.; Ponrathnam, Surendra; Chavan, Nayaku (Bulletin of Materials Science, 2015)
Non-symmetrical and linear dyad-based mesogens were synthesised containing imine or ester bridging group. In the present work, due to the absence of branching in diamine-based mesogen, the structure has-rigidity inversely imine/ester bridging groups between two benzene rings imparts-flexible property to the mesogen and consequently rigid-flexible property has been balanced. The synthesised mesogens were characterized by different techniques including nuclear magnetic resonance and Fourier transform infrared spectroscopy. Liquid crystalline polymers (LCPs) were synthesised using pyromellitic dianhydride and 4-[(4-aminobenzylidene)amino]aniline or 4-aminophenyl-4-aminobenzoate. Subsequently, thermotropic liquid crystalline polymers (TLCPs) have also been evaluated to obtain optical microscopy textures at different temperatures which demonstrated interesting and notable changes. It is worth noting that marble-like textures were observed upto 200A degrees C.
Keywords: Diamine; liquid crystalline polymer; mesogen; optical microscopy textures; pyromellitic dianhydride

Synthesis of novel silica-polyimide nanocomposite films using aromatic-amino modified silica nanoparticles: mechanical, thermal and morphological investigations - Ghorpade, Ravindra V.; Rajan, C. R.; Chavan, Nayaku; Ponrathnam, S. (Express Polymer Letters, 2015)
Silica nanoparticles were modified with aromatic amino groups and modified-silica/polyimide composite films were prepared using them. 3,3!, 4,4!-Benzophenone tetracarboxylic dianhydride (BTDA) and 4,4!-oxydianiline (ODA) were used as precursors for polyimide matrix. The structures of the modified nanoparticles and hybrid nanocomposites were identified using Fourier Transform Infrared (FTIR) spectrometry. The hybrid composite films were evaluated for mechanical, thermal and morphological characteristics. Morphological results describe a uniform dispersion of silica particles in the polymer matrix. The thermal stability and mechanical properties of polyimide composite were improved, and the decomposition temperature was increased when the amount of silica nanoparticles was increased.
Keywords: hybrid polyimide composites; mechanical properties; Nanocomposites; nanoparticle modification; Thermal properties

Thermotropic liquid crystalline polyesters derived from bis-(4-hydroxybenzoyloxy)-2-methyl-1,4-benzene and aliphatic dicarboxylic acid chlorides - Mulani, Khudbudin Baban; Momin, Mohasin Shamshuddin; Ganjave, Nitin V.; Chavan, Nayaku (Bulletin of Materials Science, 2015)
A series of thermotropic liquid crystalline polyesters derived from bis-(4-hydroxybenzoyloxy)-2-methyl-1,4-benzene(BHBOMB) and aliphatic dicarboxylic acid chlorides were investigated. All these polyesters were synthesized by interfacial polycondensation method and characterized by differential scanning calorimetry and wide-angle X-ray diffractometer. These polyesters consist of BHBOMB as a mesogenic diol and aliphatic diacid chlorides were used as flexible spacers. The length of oligomethylene units in polymer was varied from the trimethylene to the dodecamethylene groups. The transition temperatures and thermodynamic properties were studied for all these polymers. All these polyesters were soluble in chlorinated solvents such as chloroform, dichloromethane, dichloroethane, etc. More importantly, all these polyesters exhibited very large mesophase stability.
Keywords: dicarboxylic acid chloride; interfacial polycondensation; Liquid crystalline polyesters; rigid diol; thermotropic

Crosslinked polymer embedded Cu/Ag for comparative drug adsorption and kinetics evaluation - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (International Journal of Polymeric Materials and Polymeric Biomaterials, 2016)
Two-dimensional crosslinked polymer (2-DCP) was synthesized for evaluation of drug adsorption and kinetics thereof. Further, polymer properties were evaluated and parameters such as contact time and adsorption isotherm were also studied. Herein, contact time demonstrated 83% and 85% of drug loading in an acidic medium for two-dimensional crosslinked polymer embedded copper and silver (2-DCP-Cu/Ag), respectively in 24h. Initial 4h is the exponential drug loading period whereas drug loading was increased gradually after 4h. Salbutamol loading was well-fitted to Langmuir adsorption isotherm, which indicated a monolayer drug adsorption with respect to 2-DCP-Cu/Ag. Pseudo first- and pseudo second-order kinetics was evaluated to perceive the drug adsorption mechanism and equilibrium adsorption capacity. Monolayer drug adsorption with chemisorption mechanism was observed for 2-DCP-Cu/Ag. In addition to this, decomposition temperature of polymer was 440 and 325 degrees C while glass transition temperature of polymer was 280 and 200 degrees C before and after metal modification, respectively. (A=aqueous phase; B=organic phase; C=drug solution; D=drug loaded polymer; E=enlarged drug loaded polymer.) [GRAPHICS] .
Keywords: Adsorption isotherm; adsorption kinetics; crosslink polymer; drug loading; langmuir adsorption isotherm; salbutamol

Interfacial tension approach toward drug loading with two-dimensional crosslinked polymer embedded gold: adsorption kinetics evaluation - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (International Journal Of Polymeric Materials And Polymeric Biomaterials, 2016)
Interfacial tension of drugs with hydrophilic polymer (A) embedded gold resulting into selective drug adsorption, which also affected the drug adsorption kinetics. Two-dimensional crosslinked polymer embedded gold was synthesized for drug loading application in an acidic buffer. Lower interfacial tension of pantoprazole sodium (B) revealed the exponential loading inversely loading was gradual for chloroquine (C) having more interfacial tension with adsorbent. Initial 2 h was the exponential adsorption period for a pantoprazole sodium whereas exponential adsorption begins after 12 h for a chloroquine. Monolayer drug adsorption was obtained because Langmuir adsorption isotherm was obeyed by both drugs. Moreover, pseudo first-and pseudo second-order kinetics was also evaluated which demonstrated that reactive sites of the adsorbent are homogeneous and drug adsorption mechanism is chemisorption and not the physisorption. Thermal analysis was evaluated to confirm the polymer thermostability and glass transition temperature during catalytic applications in thermal reactions.
Keywords: Adsorption isotherm; adsorption kinetics; drug loading; drug polarity; Interfacial tension

Inverse high internal phase emulsion polymerization (i-HIPE) of GMMA, HEMA and GDMA for the preparation of superporous hydrogels as a tissue engineering scaffold - Nalawade, Archana C.; Ghorpade, Ravindra V.; Shadbar, Sadiqua; Qureshi, Mohammed Shadbar; Chavan, Nayaku; Khan, Ayesha A.; Ponrathnam, S. (Journal of Materials Chemistry B, 2016)
A series of novel superporous hydrogels for regenerative medicine were prepared by oil-in-water (o/w) or inverse high internal phase emulsion (i-HIPE) copolymerization of glycerol monomethacrylate (GMMA), 2-hydroxy ethyl methacrylate (HEMA) and glycerol dimethacrylate (GDMA) as a cross-linker using a non toxic solvent and a redox initiator system at the physiological temperature (37 degrees C). The monomer GMMA was synthesized from glycidyl methacrylate (GMA) by an alternative facile method using Amberlyst-15. The described i-HIPEs showed a significantly wider stability window. The polyHIPE hydrogels were characterized by FTIR, BET method for surface area, mercury porosimetry, SEM, DSC, TGA, XRD, compressive strain and strain recovery. The swelling ratio of the hydrogels and their degradation in 0.007 M NaOH and lipase B (Candida antarctica) solutions were determined gravimetrically and the rate of degradation was explained in terms of the molecular structure of the hydrogels. The morphological studies showed that the pore diameter varied between 20 and 30 mu m and the pore throats (interconnecting windows) diameter was in the range of 4-8 mu m. The described polyHIPE hydrogels were found to have an open cell morphology and interconnected pore architecture, which are important characteristics for scaffold applications. The initial cytotoxicity study performed according to ISO-10993-5 indicated cytocompatibility (97% cell viability) and the subsequent cell seeding and proliferation study exhibited 55-88% cell viability (increased monotonously from GHG-1 to GHG-5), which could be attributed to modulation of the physical and chemical properties of the hydrogels. The described super porous hydrogels are considered as potential candidates for scaffold materials in tissue engineering applications.

Role of aliphatic hydrocarbon content in non-solvating porogens toward porosity of cross-linked microbeads - Mane, Sachin; Badiger, Manohar V.; Rajan, C. R.; Ponrathnam, Surendra; Chavan, Nayaku (Polymer, 2016)
Megaporous spherical acrylate copolymer beads were synthesized by suspension polymerization using non-solvating porogens. Non-solvating porogens with higher aliphatic hydrocarbon content generated megaporous morphology with lower surface area. Surface area increased and inversely megaporosity was decreased with decrease in the aliphatic hydrocarbon content of porogen. Megaporosity (5.47 mu m) and pore volume of 5.52 cm(3)/g was obtained with n-decanol. Thermal property of copolymer is a function of type (rigidity/flexibility/elemental composition) and concentration (cross-link density) of monomer and cross-linker. Copolymer containing rigid cross-linker (divinylbenzene) had better thermal stability over copolymer with flexible cross-linker (ethylene dimethacrylate). Further, higher concentration of rigid cross-linker or lower concentration of flexible cross-linker enhanced the thermal stability. Porous polymers are potentially recognized as a solid support for solid-phase synthesis. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cross-linked microbeads; Interfacial tension; Megaporosity; Non-solvating porogens; Thermal properties

Selective solid-phase extraction of metal for water decontamination - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (Journal of Applied Polymer Science, 2016)
Metal-contaminated industrial effluent is a major concern for human health. Therefore, the removal of metal is of primary importance. In this study, metals were selectively extracted from water. Selective metal recovery was studied with a crown-ether-based polymer, wherein the selectivity was observed for strontium over lead. Parameters influencing the metal recovery, such as the contact time, adsorbent dosage, and metal-ion concentration, were evaluated. Interestingly, the adsorption rate of strontium was exponentially increased for the initial 4 h, and lead was adsorbed exponentially after 6 h. Notably, 98% strontium adsorption and 64% lead adsorption were obtained in 24 h. The Langmuir adsorption isotherm was in good agreement and demonstrated that the reactive sites of the adsorbent were homogeneous with monolayer metal adsorption with an adsorbent. The Freundlich adsorption isotherm was not obeyed by both metals. The pseudo-first-order and pseudo-second-order kinetics indicated that strontium was adsorbed by chemisorption and lead was adsorbed by physisorption. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 132, 42849.
Keywords: Adsorption; copolymers; crosslinking; kinetics; radical polymerization

Synthesis and characterization of thermally stable polyimides with a pendent phenothiazine unit based on new diamine 10-(3,5-diaminobenzoyl)phenothiazine - Ghorpade, Ravindra V.; Thorave, Asmita K.; Rajan, C. R.; Chavan, Nayaku; Ponrathnam, S. (High Performance Polymers, 2016)
A novel diamine 10-(3,5-diaminobenzoyl)phenothiazine (DBPT) with a side chain containing phenothiazine unit was synthesized. A new family of polyimides (PIs) containing phenothiazine unit in the side chains has been successfully synthesized by direct polycondensation of DBPT with pyromellitic dianhydride, 3,3',4,4'-benzophenone tertacarboxylic dianhydride, and 4,4'-oxydiphthalic anhydride (ODA) via a conventional two-step chemical imidization process. The yield of polymers was good enough, which were soluble in most organic solvents. The molecular orbital energy gaps, thermal stability, and crystallinity of PIs were investigated by molecular modeling, thermogravimetric analysis, and wide-angle X-ray scattering, respectively. Thermal properties of polymers were good enough to permit the use of these PIs in various applications; only 49% weight loss is detected at 900 degrees C in nitrogen atmosphere. X-Ray diffraction clearly reveals the amorphous nature of PIs. A quantum modeling study (density functional theory) has shown the influence of dianhydride structure on the energy difference of highest occupied molecular orbital and lowest unoccupied molecular orbital energy levels.
Keywords: phenothiazine-containing diamine; Polyimide; thermally stable polymer

Synthesis of 2-phenoxy-2-phenylethyl acrylate and copolymerization with 2-phenylethyl acrylate: estimation of monomer reactivity ratios, thermal and optical properties - Ghorpade, Ravindra V.; Ponrathnam, Surendra; Chavan, Nayaku (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2016)
A new aromatic based monomer 2-phenoxy-2-phenylethyl acrylate (PPEA) was synthesized. Copolymers of PPEA with 2-phenylethyl acrylate (PEA) were prepared by free radical polymerization. The reactivity ratios were estimated using various graphical methods. Structural parameters of the copolymers were obtained by calculating the dyad monomer sequence fractions and the mean sequence length. Optical properties of polymers such as refractive indices and UV-Visible absorption were investigated. The glass transition temperature and thermal degradation behavior of the copolymers were studied. Combined with the RI, transparency and thermal properties, prepared copolymers hold great promise as materials for intraocular lens applications.
Keywords: 2-Phenoxy-2-phenylethyl acrylate; 2-phenylethyl acrylate; copolymerization; Optical properties; reactivity ratios; Thermal properties

Thermotropic liquid crystalline polyesters derived from 2-chloro hydroquinone - Manurkar, Nagesh; More, Sayaji; Mulani, Khudbudin; Ganjave, Nitin; Chavan, Nayaku (Journal of Chemical Sciences, 2017)
Synthesis of thermotropic liquid crystalline polyesters derived from bis[4-hydroxy benzoyloxy]-2-chloro-1,4-benzene (BHBOCB) and aliphatic dicarboxylic acid chlorides by interfacial polycondensation methodology is presented. Synthesised polyesters consist of bis[4-hydroxy benzoyloxy]-2-chloro-1,4-benzene as a mesogen and aliphatic diacid chloride as flexible spacer. The length of oligomethylene units in the polymer was varied from the trimethylene to the dodecamethylene groups. Synthesized polyesters were characterized by differential scanning calorimetry and optical microscopy. The transition temperatures and thermodynamic properties were studied for all these polymers. These polyesters exhibited thermotropic liquid crystalline behavior and showed nematic texture except decamethylene spacer. Decamethylene spacer based polyester showed marble texture of smectic C. Mesophase stability of these polyesters was higher than (except first heating cycle of PE-1).  SYNOPSIS The present study deals with the synthesis of thermotropic liquid crystalline polyesters derived from bis[4-hydroxy benzoyloxy]-2-chloro-1,4-benzene (BHBOCB) and aliphatic dicarboxylic acid chlorides by interfacial polycondensation methodology.
Keywords: acid; Aliphatic Flexible Spacers Main-chain; Aromatic Mesogen; Elastomer; Morphology; Polydomain; Polymers; Thermotropic Liquid Crystalline Polyesters; Units

Adsorptive removal of chromium(VI) using spherical resorcinol-formaldehyde beads prepared by inverse suspension polymerization - Mulani, Khudbudin; Patil, Vishwanath; Chavan, Nayaku; Donde, Kamini (Journal of Polymer Research, 2019)
The spherical cross-linked beaded polymers were prepared by condensation of resorcinol and formaldehyde in presence of tri-ethylamine by inverse suspension polymerization technique. The m-cresol, aniline, urea and thiourea were used as co-monomer and polyethylene glycol (PEG 400) was used as porogen. Paraffin oil was used as non-aqueous suspension agent. The polymeric spherical beads were prepared using various types of comonomers exhibiting range of particle size 77.62 to 158.84m at 90 degrees C and 300rpm for 4h. The resulting beads were analyzed by elemental analysis, particle size analysis and scanning electron microscope (SEM). The synthesized beads were used for the removal of Cr(VI) from aqueous solutions. A simple and sensitive solid phase extraction procedure was used for the determination of chromium at trace level by spectrophotometric method using 1,5-diphenylcarbazide reagent. The adsorption of Cr(VI) on the resorcinol-formaldehyde beads was monitored by energy-dispersive X-ray spectroscopy (EDX) analysis. The metal adsorption parameters such as contact time, pH, metal ion concentration and adsorbent dose were investigated. For Cr(VI), the maximum adsorption capacity was about 99% at pH2 for the resorcinol-formaldehyde beads obtained.
Keywords: adsorption kinetics; Beads; Chromium (VI); Formaldehyde; Inverse suspension; Resorcinol

Novel shear thickening fluids possessing high shear rates using monodispersed silica nanoparticles and PEG - Chavan, Nayaku; Dhage, Atul; Wale, Apparav; Thorave, Asmita; Rajdeo, Kishor; Kamble, Sanjay; Ponrathnam, Surendra; Tambe, Sanjeev; Verma, Sanjeevkumar (Polymer Bulletin, 2023)
Higher shear rate possessing homogeneous shear thickening fluids were synthesized using monodispersed silica nanoparticles and polyethylene glycol (PEG). Novel homogeneous methodology was developed for the synthesis of shear thickening fluids using monodispersed silica nanoparticles and PEG. Shear rate of shear thickening fluids (STF) was determined using rheometer at room temperature. The normal shear rate was observed in the range of 100 to 1200 s(-1), whereas higher shear rate 2000 s(-1) was obtained using monodispersed silica nanoparticles, PEG and shear rate enhancer. Monodispersed silica nanoparticles were synthesized in a typical one-pot using modified Stober's method at room temperature. Precursors were used for the synthesis of monodispersed silica nanoparticles such as tetraethyl orthosilicate (TEOS), ethanol, deionized water and ammonia as catalyst. Particle size of monodispersed silica nanoparticles was in the range of 100-1200 nm, and particle size distribution was varied from 0.000 to 0.221. Synthesis of monodispersed silica nanoparticles was studied by various parameters, namely effect of TEOS concentration, grade of ethyl alcohol, ammonia concentration and water concentration. TEOS concentration effect shows particle size and particle size distribution increases with increase in concentration of TEOS. Even though concentration of TEOS was increased up to 5 times the observation was same for all particle sizes such as 100, 300 and 500 nm. Particularly in the case of 300 nm monodispersed silica nanoparticle synthesis, as TEOS concentration was increased from 1 to 5X (5 times) the particle size was increased from 331.7, 447.8, 497.0, 512.0 and 531.7 nm and particle size distribution was 0.005, 0.000, 0.006, 0.007 and 0.089, respectively. The effect of grade of ethyl alcohol illustrates that Indian rectified spirit shows almost similar results with respect to China make ethyl alcohol. Comparative study of China and Indian rectified spirit shows silica nanoparticle size was 174.6 and 174.2 nm, and particle size distribution was 0.065 and 0.071, respectively. Ammonia concentration effect explains particle size and particle size distribution increases with increase in concentration of ammonia. Water concentration effect shows particle size and particle size distribution increases with increase in concentration of ammonia. Comparative data of water concentration effect for 1316 and 1974 mL shows particle size were 321.7 and 488.0 nm, and particle size distribution was 0.083 and 0.05, respectively, under similar conditions. Morphological studies displayed the shape of the silica nanoparticles was spherical, monodispersed and isolated. A typical TEM image of monodispersed silica nanoparticles for 500 nm was observed with extremely low polydispersity, i.e., 0.000. It is very difficult to get such a type of excellent photograph of monodispersity by Stober's method particularly on large scale. Rheology study of homogeneous shear thickening fluids studied by varying the parameters such as composition of silica nanoparticles with PEG, effect of amount of solvent, effect of refluxing time, effect of additive with respect to the mol. wt. of PEG and effect of additive such as Tannin. All these parameters of STF explored with respect to the shear rate and shear viscosity. Effect of ethanol amount on STF demonstrates the shear rate increases with increase in amount of solvent. Effect of refluxing time on STF exhibits the shear rate increases with increase in refluxing time. Effect of composition based on 500 nm monodispersed silica nanoparticles and PEG 200 with respect to 60:40, 65:35 and 70:30 composition was studied and the results predict that shear rate increases with increase in silica percentage in composition, i.e., 118, 265 and 1200 s(-1) for 60:40, 65:35 and 70:30 composition, respectively, whereas maximum viscosity decreases with increase in silica content, i.e., 2.559, 1.420 and 1.200 Pa.s for 60:40, 65:35 and 70:30 composition, respectively. Effect of additive on shear rate and shear viscosity illustrates that shear rate decreases with increase in additive percentage in composition, whereas maximum viscosity increases with increase in additive content. Effect of additives on shear rate and shear viscosity was performed using 65:35 composition with respect to PEG 200 along with PEG 6000 shows shear rate was decreased from 142 to 6.42 s(-1) and maximum viscosity was increased from 56.1 to 571.0 Pa.s when the quantity of PEG 6000 was doubled. In general, additive decreases shear rate and increases shear viscosity (maximum). But effect of Tannin as an additive on 500 nm monodispersed silica nanoparticles with PEG 200 using 70:30 composition showed enormous increase in shear rate, i.e., 2000 s(-1). This is anomalous behavior of additive was observed.
Keywords: Monodispersed silica nanoparticles; Nanocomposite; Polyethylene glycol; Shear rate; Shear thickening fluid